Parasocial Interaction on Indonesia’s Beauty Influencer: Antecedents and Consequences - Putri Linggasari Sofi; Indira Rachmawati (Jurnal Syntax Transformation, 2024)
Consumers' dependence on product reviews provided by other consumers makes consumers make social media influencers (SMI) a source of information and reference before purchasing products. The influence of SMI on their followers has led many beauty marketers to use social media influencers to communicate their products. However, the increasing use of influencer marketing by marketers has led to consumer suspicion of the authenticity of influencers. Therefore, based on the stimulus-organism-response (SOR) framework, this study analyzes consumer behavior through the content attributes and interaction strategies exposed by social media influencers to followers, leading to consumers' internal perceptions of parasocial interaction, hedonic value, and utilitarian, and ultimately influencing consumers' response of purchase intention. This study used PLS-SEM as a data analysis technique using a sample of 363 respondents. The PLS-SEM results revealed that content attributes (i.e., attractiveness and prestige) and interaction strategies (i.e., interactivity) positively influence parasocial interaction and, in turn, lead to purchase intention. The results also show that parasocial interaction has a significant effect on hedonic (perceived transparency and perceived enjoyment) and utilitarian (informativeness and credibility) responses. It was also found that hedonic (perceived enjoyment) and utilitarian (credibility) responses significantly influenced purchase intention. Meanwhile, the hedonic response (perceived transparency) and utilitarian response (informativeness) did not significantly affect followers' purchase intention. This research demonstrates the role of content attributes and interaction strategies in creating parasocial interactions and the effects of parasocial interactions on hedonic, utilitarian and purchase intention responses. Based on the results of this study, marketers and influencers are advised to build intimate relationships with the audience to increase purchase intention. This relationship-building can be created through high interactive power, attractiveness, and prestige content. Then, it is also recommended to pay attention to aspects of audience comfort and maintain the credibility of influencers to shape the buying interest of the audience of social media influencer content.